2023
DOI: 10.1038/s41598-023-45132-0
|View full text |Cite
|
Sign up to set email alerts
|

Host fecal DNA specific methylation signatures mark gut dysbiosis and inflammation in children affected by autism spectrum disorder

Mariella Cuomo,
Lorena Coretti,
Davide Costabile
et al.

Abstract: The gut-brain axis involves several bidirectional pathway communications including microbiome, bacterial metabolites, neurotransmitters as well as immune system and is perturbed both in brain and in gastrointestinal disorders. Consistently, microbiota-gut-brain axis has been found altered in autism spectrum disorder (ASD). We reasoned that such alterations occurring in ASD may impact both on methylation signatures of human host fecal DNA (HFD) and possibly on the types of human cells shed in the stools from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The study found that specific epigenetic features in the DNA of gut microbes in human feces, particularly those associated with inflammation, are strongly associated with disease ( 59 ). In our study, we found some possible inflammatory cytokine pathways in the gut microbiota associated with the epigenetic clock.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that specific epigenetic features in the DNA of gut microbes in human feces, particularly those associated with inflammation, are strongly associated with disease ( 59 ). In our study, we found some possible inflammatory cytokine pathways in the gut microbiota associated with the epigenetic clock.…”
Section: Discussionmentioning
confidence: 99%